Information technology. International standardized profile RC. X.25 protocol relaying. Definition of profile RC51.1121, X.25 protocol relaying between CSMA/CD LAN subnetworks and PSDNs using virtual calls over a digital data circuit/CSDN leased line permanent access Part 6, (15th September 1995) - British Standards Institution
No abstract available